2009
DOI: 10.1111/j.1467-9450.2009.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Working memory, deafness and sign language

Abstract: Working memory (WM) for sign language has an architecture similar to that for speech-based languages at both functional and neural levels. However, there are some processing differences between language modalities that are not yet fully explained, although a number of hypotheses have been mooted. This article reviews some of the literature on differences in sensory, perceptual and cognitive processing systems induced by auditory deprivation and sign language use and discusses how these differences may contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 129 publications
5
30
0
Order By: Relevance
“…One possibility is that the bilateral superior parietal activation found for working memory for sign language compared to speech at least partially reflects processing of the formational features of gestures in the capacity-limited store for the representation of the visual scene. This notion is in line with previous proposals that this activation reflects generation of a virtual spatial array (Rönnberg et al, 2004;Rudner et al, 2007) supporting order processing (Rudner et al, 2009). …”
Section: Working Memory For Manual Gestures 13supporting
confidence: 92%
See 2 more Smart Citations
“…One possibility is that the bilateral superior parietal activation found for working memory for sign language compared to speech at least partially reflects processing of the formational features of gestures in the capacity-limited store for the representation of the visual scene. This notion is in line with previous proposals that this activation reflects generation of a virtual spatial array (Rönnberg et al, 2004;Rudner et al, 2007) supporting order processing (Rudner et al, 2009). …”
Section: Working Memory For Manual Gestures 13supporting
confidence: 92%
“…A body of work has investigated working memory for sign language and found that although it is functionally similar to working memory for speech and supported by similar neural mechanisms, there are language modality specific differences in the neural networks that support working memory (for a review see Rudner, Andin & Rönnberg, 2009). In particular, working memory for sign language specifically recruits bilateral superior parietal regions associated with visuospatial processing (Bavelier, Newman, Working memory for manual gestures Mukherjerr, Hauser, Kemeny, Braun & Boutla, 2008;Rönnberg, Rudner & Ingvar, 2004;Rudner, Fransson, Nyberg, Ingvar & Rönnberg, 2007).…”
Section: Working Memory For Manual Gestures 13mentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have found differences in the verbal short term memory of deaf people, which may be due to the nature of sign language and/or different neural organization (Emmorey & Wilson, 2004;Rudner, Andin, & Ronnberg, 2009;Wilson & Emmorey, 1997). It is important for researchers who might want to use these norms to consider differences in articulation rates and phonological similarity for signs versus spoken words which may influence memory capacity, encoding and retrieval (see Wilson & Emmorey, 2000 for a review), and normative differences in memory for serially presented material in deaf people (Boutla, Supalla, Newport, & Bavelier, 2004), such as the tendency to show less temporal order effect in free recall tasks (Bavelier et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous research has shown, in support of the multimodal nature of the ELU model, that signers and speakers perform at similar levels on WM tasks presented either in their preferred language modality or in a format that is language modality neutral (Andin et al, 2013;Boutla, Supalla, Newport & Bavelier, 2004;Rudner, Fransson, Ingvar, Nyberg & Rönnberg, 2007). However, there are differences in the neural organization of WM for sign and speech suggesting that at least partially different underlying mechanisms come into play when explicit WM processing is engendered, for example when executive functions are engaged (Rudner et al, 2007) or load is high (Rönnberg, Rudner & Ingvar, 2004; for a review see Rudner, Andin & Rönnberg, 2009). The main goal of the present study was to determine whether preexisting semantic and phonological representation in the sign-based mental lexicon improves WM performance in the visuospatial domain and whether such representation mitigates the effect of increasing memory load, in line with the prediction of the ELU model .…”
Section: Introductionmentioning
confidence: 99%